2011
DOI: 10.1108/13287261111164853
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of podcasting in developing higher education institutions

Abstract: PurposeThe purpose of this paper is to report on podcasting experience by faculty and students in a South African higher education institution (HEI), identify issues, limitations and discuss implications for the design of future tools.Design/methodology/approachThis work consisted of two parts: semi‐structured interviews with lecturers, content/curriculum developers and a student survey.FindingsRogers's diffusion of innovations theory provided the framework for this research including determining how new innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…Two previous studies (Chaputula 2012;Nyirongo 2009) have independently shown that MZUNI has been investing in computer and Internet technologies. Given the availability of computer and Internet technologies, the assumption could be that students use Web 2.0 technologies for academic purposes, as is the case in other institutions of higher learning (see Hartshorne & Ajjan 2009;Huang, Hood & Yoo 2013;Mugwanya, Marsden & Boateng 2011;Sadaf, Newby & Ertmer 2012). This study therefore sought to investigate the use of Web 2.0 by students in the Faculty of ISC.…”
Section: Problem Statement and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two previous studies (Chaputula 2012;Nyirongo 2009) have independently shown that MZUNI has been investing in computer and Internet technologies. Given the availability of computer and Internet technologies, the assumption could be that students use Web 2.0 technologies for academic purposes, as is the case in other institutions of higher learning (see Hartshorne & Ajjan 2009;Huang, Hood & Yoo 2013;Mugwanya, Marsden & Boateng 2011;Sadaf, Newby & Ertmer 2012). This study therefore sought to investigate the use of Web 2.0 by students in the Faculty of ISC.…”
Section: Problem Statement and Research Questionsmentioning
confidence: 99%
“…Web 2.0 technologies Sandars and Schroter (2007) The study revealed that although the overall adoption of Web 2.0 was relatively high, the application of some technologies such as podcasts was still marginal and there was a need to research more on some basic concepts such as awareness and familiarity for it to hold its ground. In this context, according to Ajjan and Hartshorne (2008), Mugwanya, Marsden andBoateng (2011), Sadaf, Newby andErtmer (2012) and Huang, Hood and Yoo (2013), awareness means students' knowledge about the existence of Web 2.0 technologies, whereas familiarity refers to the skills and abilities for operating or using the Web 2.0 technologies. Some students in South Africa have misconceptions about some Web 2.0 technologies, podcasts in particular, because of a lack of knowledge, familiarity and awareness, according to the findings reported by Mugwanya, Marsden and Boateng (2011).…”
Section: Awareness Of and Familiarity Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches use a lecture recording search engine specifically for academic content, or use podcasting as an easy distribution channel for lecture recordings [19], [20].…”
Section: Generating Oer By Recording Lecturesmentioning
confidence: 99%
“…Therefore, too little attention is ultimately given to the design, implementation and evaluation of mobile education systems, despite advances in technology and a clear compelling case to support their utilization. There is a need within mobile-education research to invest in matching requirements more closely with design, while applying human centered design approaches (Mugwanya & Marsden, 2011). This paper explores how adopting a Participatory Action Research (PAR) approach gave rise to our first software prototype, and presents the challenges faced as well as future plans.…”
Section: Introductionmentioning
confidence: 99%